Kognitive Dissonanz in der BANI-Wirtschaft: Strategien zur Bewältigung von Spannungen in der aktuellen Arbeitswelt - Marcel Dulgeridis; Lisa Schattenberg; Christian Schattenberg (IU Internationale Hochschule, 2024)
This paper delves into the increasing difficulties posed by dissonance, in the BANI (Brittle Anxious Nonlinear Incomprehensible) business setting. Cognitive dissonance refers to a clash stemming from beliefs or actions and is on the rise in contemporary work environments due to swift technological advancements and intricate decision-making processes in unstable and delicate systems. The research examines the repercussions of dissonance on organizational decision-making processes as well, as innovation and overall welfare. This study looks at the BANI framework to pinpoint factors that worsen conflict and suggests ways to deal with it like building resilience and mindfulness techniques as well, as adaptive management strategies in order to lower stress levels and improve adaptability within organizations facing uncertainty, in the business environment.
Keywords: 650; Achtsamkeit; Adaptive Managementstrategien; Arbeitswelt; BANI-Umgebung; Entscheidungsfindung; Innovation; Kognitive Dissonanz; Organisatorische Transformation; Psychologischer Stress; Resilienz; Unsicherheit; Komplexität; Konfliktmanagement